Analysis of Quality Improvement of Wood Powder Raw Materials at CV. NKM Using FMEA and FTA Methods - Muhammad Fairuz Baad; Deny Andesta; Hidayat Hidayat (G-Tech: Jurnal Teknologi Terapan, 2025)
CV. NKM is a supplier company that takes manufacturing plant waste in the form of sawdust, especially waste from merbau wood, sent to factories whose main raw material is sawdust such as pallet factories, briquettes, etc. In every process there are defects such as powder mixed with other sizes, smelly and moldy powder, and wet powder. In every process there are defects such as powder mixed with other sizes, smelly and moldy powder, and wet powder.  These defects are due to human factors, tools/machines, storage, etc. So this research was conducted using the FMEA (Failure Mode and Effect) method used to determine the severity, occurrence, and detection levels, so that the highest RPN value of 576 was obtained, namely powder mixed with other sizes and FTA produced basic events from the highest RPN value, namely lack of rest hours, lack of supervision, and lack of routine control. After the results are known, an improvement proposal will be given for the highest RPN value, namely providing sufficient hours of rest and enforcing routine control of the tool/machine.